Investigating rationales of Malaysia quality of life and wellbeing components and indicators - Mohamed Osman, Mariana; Abu Bakar, Aisyah; Bachok, Syahriah; Ibrahim, Mansor (Elsevier, 2016)
This paper reviews the formulation of Malaysia Quality of Life Reports published in 1999, 2002, 2004 and 2011 as well as Malaysia Wellbeing Report published in 2013. The reports are Malaysia Economic Planning Unit's (EPU) committed approaches to measuring the impact of economic development on Malaysia social development through a set of social indicators. This paper evaluates the rationales of the components and indicators and reveals the changes made in the reports. The document analysis identified gaps in the objective measurement of quality of life and wellbeing towards improvements in future reports.